Mythe Et réécriture du mythe de la reine de Saba dans la littérature algérienne d’expression française (Revue El-Wahat pour les Recherches et les Etudes, 2021)
Belkis, the fascinating Queen of Saba, could she be overshadowed when she remains a great mystery until today? Her story is well known to the followers of the three great Abrahamic religions. Countless Authors in world literature have sought to pierce the myth surrounding this female figure with symbols or characters. They intend presenting her by rewriting new characters reflecting the desires of various societies through her qualities like revolt, sensuality and resistance. Belkis is presented as Nedjma "the Wild Woman" by Kateb Yacine as one of of these updates of the myth of the Queen of Seba. It seems to have inspired this Algerian author who associates the character “Nedjma” with the image of resistant Algeria in her fascinating and repulsive qualities.From this reconciliation, we wanted to understand the features and mechanisms of transposition used by Kateb to operate between these two figures: Belkis and Nedjma who represent two heroines of beauty and seduction. For this, we will analyze the transposition of one figure on the other, to see then, the characteristics of their appearance and their presence through the various literature writings attributed to this myth. Keywords – rewriting - Queen of Saba - Nedjma - Transposition - Wild woman - Myth - Algerian literature of French expression.